ABx-type amphiphilic macromonomer-based supramolecular hyperbranched polymers for controllable self-assembly. Issue 8 (3rd February 2017) - Liu, Tingting; Wang, Shuodong; Song, Yanli; Li, Jiawei; Yan, Hongxia; Tian, Wei
Abstract : A novel supramolecular hyperbranched polymer (SHP) is constructed through using an AB x -type amphiphilic macromonomer. The obtained SHP can form ellipsoidal unimolecular micelles and branched aggregates under different solution conditions. Abstract : A macromonomer strategy has displayed potential advantages of constructing functional supramolecular hyperbranched polymers (SHPs); however, owing to the limited functional group number and weak noncovalent interactions, it is difficult to control the dynamic self-assembly process of SHPs based on the reported AB2 -type hydrophilic macromonomers. In this work, a novel SHP was first constructed using an AB x -type ( x > 2) amphiphilic macromonomer for tuning its self-assembly morphology, size and dynamic process. The obtained SHPs formed ellipsoidal unimolecular micelles with sizes of approximately 10 nm by directly dissolving SHP precursors in a 0.5 mol L −1 NaCl solution. These unimolecular micelles further self-assembled into branched aggregates in aqueous solutions after the removal of NaCl. SHP-based unimolecular micelles present a higher sensitivity for drug sensing in comparison with further branched self-assemblies. Obtaining SHPs through the AB x -type amphiphilic macromonomer may be a novel strategy to deeply investigate the relationships between polymer structures and self-assemblies and regulate their functionality.